Scimitar syndrome: unveiling the complexities of a rare congenital cardiopulmonary anomaly - Nargis Mateen; Abraam Rezkalla; Nagihan Orhun (European Journal of Case Reports in Internal Medicine, 2025)
Scimitar syndrome is a rare congenital anomaly characterised by anomalous pulmonary venous drainage of the right lung into the inferior vena cava, often accompanied by right lung hypoplasia and dextroposition of the heart. Here, we present the case of a 24-year-old female with scimitar syndrome and a history of asthma who presented with acute exacerbation of asthma. A chest X-ray revealed opacification of the right hemithorax, and a CT angiography revealed congenital hypoplasia of the right lung and dextrocardia. This report provides a detailed description of scimitar syndrome to spread awareness of this rare diagnosis and highlights the unique and various constellations of anatomical abnormalities seen in scimitar syndrome that make diagnosis difficult.